MENINGKATKAN MOTIVASI BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN THINK PAIR SHARE PADA MATERI POKOK SURAT LAMARAN PEKERJAAN - Retni Suharianti (EDUCATE, 2023)
This research was conducted at SMA Negeri 2 Tebing Tinggi, with the type of research namely "Classroom Action Research". The subjects in this research were 35 Class 12 IPA1 students. The object of this research was the Think Pair Share learning model which gives students the opportunity to think, answer and help each other. And the tools used to collect data are observation sheets and tests. Observations are carried out to observe the activities of teachers and students in learning and tests are given to see the level of student success in the teaching material presented. The problem faced in this research is the lack of understanding of students in mastering Indonesian language learning material because in the learning process the teacher only relies on the material and uses the lecture method so that students are less active in learning Indonesian. This research aims to find out whether using the Think Pair Share learning model can improve the learning outcomes of Class 12 Science 1 students at SMA Negeri 2 Tebing Tinggi FY 2023-2024. The hypothesis proposed in this research is "Student learning outcomes on the main material of job application letters will increase if the Think Pair Share learning model is used. Based on the results of observations made in the initial conditions, there were 21 students out of 35 students or around (60%) who were not motivated to learn so only 3 students managed to complete or 8.57%. A total of 14 students out of 35 students or around (40%) were motivated. Then in cycle I there were 19 students out of 35 students or around (54.28%) who were motivated by the completeness of learning outcomes, 19 students or around 54.29% and 16 students out of 35 students or around (45.71%) who are not yet motivated. In cycle II there were 31 students out of 35 students or around (88.57%) who were well motivated with complete learning outcomes of 31 people or 88.57%, and as many as 4 students or around (11.43%) who not motivated. Based on the results of the research starting from the initial conditions, cycle I and cycle II there has been a significant increase. Thus, it can be concluded that using the Think Pair Share learning model can increase students' motivation to learn Indonesian on the main subject of job application letters in class 12 Science 1 SMA Negeri 2 Tebing Tinggi FY 2023-2024.